Aesthetic Study of The Philosopher’s Opinions and Islamic Sources - Noori, Abdul Haq; Samimi, Shirali (IJLHE: International Journal of Language, Humanities, and Education, 2023)
Beauty is one of the three concepts to which value judgments are attributed. Immanuel Kant, the great German philosopher (1724-1804 AD), stated that beauty is something that arouses the satisfaction of the soul without the need for imagination. In other words, beauty is what makes us feel happy without seeing it and also without any apparent benefit. The relation of beauty and ugliness to passivity is analogous to the relation of good and evil to action and the relation of right and wrong to reason. Beauty is synonymous with goodness and virtue, signifying proportion and harmony between the components of an object. It is mentioned in the authoritative book of hadith (Muslim Sharif) that "Allah is the most beautiful of the beloved," implying that God (the Exalted) is beautiful and loves beauty. Additionally, divine verses and signs, by reminding us of the manifestations of beauty in creation, prompt humans to admire their creator based on the manifestations of existential creation. They also encourage us to recognize that the beauty of human creation encompasses the earth, sky, stars, and more. Everyone is invited and guided to God through these manifestations.